An Economic Analysis of Tourism Contribution for Urban Poverty Reduction in Major Tourist Towns of North Shewa Zone, Amhara Region, Ethiopia. (30th September 2022) - Fikire, Abebaw Hailu; Bires, Zemenu; Emeru, Girma Mulugeta
Abstract : Tourism has a significant contribution to the livelihood diversification of the communities and supporting economic development efforts. This study aimed at an economic analysis of tourism's contribution to urban poverty reduction in Major Tourist Towns of North Shewa Zone, Amhara Region, Ethiopia. A multistage simple random sampling and purpose sampling were used to select sample respondents from the population in the study area. Hence, a total of 286 valid observations from 385 sample respondents were used for the analysis of the collected data. Both descriptive and inferential statistics were used to analyze the data. The finding of this study revealed that tourism has a significant and positive contribution to poverty reduction in urban areas, but the level of contribution is minimal. Besides, it exhibited that funding aids and government concern for tourism-targeted programs and access to credit infrastructure, tourism education, and policy were the significant factors that affect tourism's role in urban poverty reduction. Thus, to enhance its contributions and overcome industry bottlenecks, the government shall put tourism as a valuable development pillar, develop pro-poor strategies linking tourism with the urban poor, develop urban tourism development programs, and assign tourism-trained professional leaders to the sector.